2016
DOI: 10.1590/1678-98652016000400010
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intake and overall diet quality of female soccer players before the competition period

Abstract: Objective: To assess the dietary intake and overall diet quality of female soccer players before the competitive games. Methods: This descriptive and cross-sectional study included 21 women aged 20.8±4.5 years from a professional soccer team. Their nutritional status and dietary adequacy during the training period, before competition season, were assessed. Dietary intake was assessed by three 24-hour recalls, one food frequency questionnaire, and the Healthy Eating Index, an overall diet quality index based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 21 publications
3
42
3
6
Order By: Relevance
“…The study showed that athletes' EE averaged 2,501 kcal/day, with no significant differences between tennis (2,557 kcal/day) and soccer (2,485 kcal/day) players. The EE values of this study were similar to those in the previous studies that have shown daily EE values to be 2,780kcal among female tennis players (Ndahimana, et al, 2017) and between 2,274kcal and 2,925kcal among soccer players (Mara, et al, 2015;Santos, et al, 2016). It is noteworthy that Ndahimana et al (2017) study did not report the expertise level of the tennis players or how many practices or games the sample had during their study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The study showed that athletes' EE averaged 2,501 kcal/day, with no significant differences between tennis (2,557 kcal/day) and soccer (2,485 kcal/day) players. The EE values of this study were similar to those in the previous studies that have shown daily EE values to be 2,780kcal among female tennis players (Ndahimana, et al, 2017) and between 2,274kcal and 2,925kcal among soccer players (Mara, et al, 2015;Santos, et al, 2016). It is noteworthy that Ndahimana et al (2017) study did not report the expertise level of the tennis players or how many practices or games the sample had during their study.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the importance of energy balance to female athletes' performance and health (Clarke, Reed, Crouse, & Armstrong, 2003;Mara, et al, 2015;Maughan & Shirreffs, 2007;Ndahimana, et al, 2016;Santos, et al, 2016), the efforts to understand college student-athletes' EE and dietary intake are well warranted. The study showed that athletes' EE averaged 2,501 kcal/day, with no significant differences between tennis (2,557 kcal/day) and soccer (2,485 kcal/day) players.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations